If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14x + -159 = 5x + -6 Reorder the terms: -159 + 14x = 5x + -6 Reorder the terms: -159 + 14x = -6 + 5x Solving -159 + 14x = -6 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -159 + 14x + -5x = -6 + 5x + -5x Combine like terms: 14x + -5x = 9x -159 + 9x = -6 + 5x + -5x Combine like terms: 5x + -5x = 0 -159 + 9x = -6 + 0 -159 + 9x = -6 Add '159' to each side of the equation. -159 + 159 + 9x = -6 + 159 Combine like terms: -159 + 159 = 0 0 + 9x = -6 + 159 9x = -6 + 159 Combine like terms: -6 + 159 = 153 9x = 153 Divide each side by '9'. x = 17 Simplifying x = 17
| 4x-4y=3x+5 | | 2(8x+3)=22-8x | | 14x-159= | | 72=2x+25-15 | | 5x-y+z=-18 | | 3x+10=-10-7 | | 9n=-6 | | 3n+7=n+10 | | -7+21= | | (5y^2+4y-4)-(6y^2-7y-8)= | | n^2-10n-16=-9 | | 2x+2+x=180 | | -16-u=-14 | | 6+5w=5w-3 | | 4-5m=10-7m | | 4(2a+2)=16 | | -3x-7(x-2)=94 | | 2.6x-5.7=-14.02 | | 3x-13-5x=4x+11 | | (y^4+5)(-8y^2)= | | 3(3x-2)=-18 | | f(x)=n+5 | | 3x-7=9-x+4 | | 5+3m=-10 | | (a-3)(4a^2-9a-3)= | | y=4x^2-8x-2 | | 8+7x=-13 | | (a-3)(4a-9a-3)= | | -4x-8=2x+10 | | 9x-8y=10 | | 2(x-6)=3(x-2) | | -5x+7y=-18 |